2012
DOI: 10.18433/j3qk57
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cyclosporin A and Tacrolimus on Magnesium Influx in Caco2 Cells

Abstract: PURPOSE: Hypomagnesemia with urinary magnesium (Mg) wasting is a well acknowledged side effect of cyclosporin A (CsA) and tacrolimus (FK506) treatments. TRPM6, TRPM7 and MagT1 are involved in the active transcellular Mg transport processes in intestine and kidney. Since Mg homeostasis is tightly controlled by the dynamic action of intestinal absorption of dietary Mg and renal excretion of Mg, we investigated whether CsA and FK506 in commercially available solutions for clinical use decrease the expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…One known side effect of calcineurin inhibitors is hypomagnesemia. Cyclosporin A and FK506 (tacrolimus), important calcineurin inhibitors, affect Mg flux as assessed by MagFura measurements in the intestinal epithelial cell line CaCo (Gouadon et al 2012). While cyclosporin A counteracts Mg accumulation, FK506 increases Mg influx without altering expression levels of TRPM6, TRPM7, or MagT1.…”
Section: A Biophysical Description Of the Channel Function Permeatmentioning
confidence: 99%
“…One known side effect of calcineurin inhibitors is hypomagnesemia. Cyclosporin A and FK506 (tacrolimus), important calcineurin inhibitors, affect Mg flux as assessed by MagFura measurements in the intestinal epithelial cell line CaCo (Gouadon et al 2012). While cyclosporin A counteracts Mg accumulation, FK506 increases Mg influx without altering expression levels of TRPM6, TRPM7, or MagT1.…”
Section: A Biophysical Description Of the Channel Function Permeatmentioning
confidence: 99%
“…Hypomagnesemia with urinary magnesium excretion is a well-known adverse effect of tacrolimus treatment in solid-organ transplant recipients. 20 Woodside and associates 21 demonstrated that calcineurin inhibitors caused hypomagnesemia in patients with renal transplant. In adult renal transplant recipients, the prevalence of hypomagnesemia was found to range from 10.2% to 43%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent studies link the cyclosporineinduced hypomagnesemia with hampered EGF signaling toward TRPM6 [77,78 & ]. In addition, Gouadon et al [79] used Caco2 cells to determine differential effects of cyclosporine and tacrolimus on Mg 2þ influx without altering expression of TRPM6 or other Mg 2þ transporters. Fourth, in 1979, hypomagnesemia was established as a serious side-effect in patients receiving cisplatin chemotherapy [6].…”
Section: Transient Receptor Potential Melastatin 6 and Its Regulatorymentioning
confidence: 99%